ChemInform Abstract: γ‐Aminoalcohol Rearrangement Applied to Pentahydroxylated Azepanes Provides Pyrrolidines Epimeric to HomoDMDP. Issue 28 (25th June 2015) - Jagadeesh, Y.; Tran, A. T.; Luo, B.; Auberger, N.; Desire, J.; Nakagawa, S.; Kato, A.; Zhang, Y.; Sollogoub, M.; Bleriot, Y.
Abstract A short sequence is described for the conversion of azepanes (I) and (V) into pyrrolidines (IV) and (VIII), which are epimeric to α‐glucosidase inhibitor homoDMDP.